Do positive childhood and adult experiences counter the effects of adverse childhood experiences on learned helplessness? - Crandall, AliceAnn; Castaneda, Gladys Lopez; Barlow, Melissa J.; Magnusson, Brianna M. (Frontiers in Child and Adolescent Psychiatry, 2024)
Introduction Learned helplessness often arises when an individual feels that a challenging situation is inescapable. Childhood trauma can lead to feelings of learned helplessness in youth and adulthood. Resiliency theory suggests that positive experiences in childhood and adulthood may counteract traumatic experiences in childhood and reduce learned helplessness and promote learned optimism, the antithesis of learned helplessness. The purpose of this study was to examine the relationship of adverse childhood experiences (ACEs) with learned helplessness and optimism in adulthood and whether positive childhood and adult experiences (PCEs and PAEs) can lessen learned helplessness even in the presence of ACEs and promote greater learned optimism. Methods The sample consisted of 435 adults who were recruited to participate in the study through Amazon Mechanical Turk (MTurk), a crowdsourcing recruitment service. Participants lived in the United States and were 18–56 years at the time of the study. Each participant completed a survey about their childhood and adulthood experiences and learned helplessness and optimism as an adult. Data were analyzed using structural equation modeling (SEM) in Mplus Version 7. Results The learned helplessness scale had two factors which we termed learned helplessness and learned optimism. ACEs were associated with higher self-report of learned helplessness and lower learned optimism. When PCEs were added to the model, ACEs retained their relationship with learned helplessness but were no longer associated with learned optimism. PCEs were positively associated with learned optimism but were not associated with learned helplessness. PAEs were negatively correlated with learned helplessness and positively correlated with learned optimism. Learned optimism and learned helplessness in adults were inversely correlated. Discussion Potentially traumatic experiences in childhood, as measured by ACEs, may lead to more learned helplessness throughout life. However, positive experiences in both childhood and adulthood can increase learned optimism, which was correlated with lower learned helplessness, even when childhood trauma was experienced.